Estimation of Economical Validity of Usage Remote Operated Disconnectors for 110kV Switchgear Schemes From Optimal Reliability Level Point of View - Lvovs, Aleksandrs; Mutule, Anna (Electrical, Control and Communication Engineering, 2011)
The paper gives results of technical and economical calculations performed for estimation of validity of usage remote operated disconnectors for most commonly used 110kV switchgears from optimal reliability level point of view. Paper contains description of performed technical calculations - calculations of 110kV switchgear schemes' reliability level depending on type of disconnectors installed, and economical calculations, that are related with additional costs of Transmission System Operator and changes in total customer costs of power supply interruptions.